Dietary disclosures: how important are non-financial interests?. (12th April 2018) - Schwab, Tim
Abstract : A recent opinion article called for nutrition researchers in particular to declare non-financial interests that might be seen to bias their work, including their own dietary preferences. But is this practicable or desirable? asks Tim Schwab